ISOLATION, QUANTIFICATION, AND IDENTIFICATION OF ROSMARINIC ACID, GAS CHROMATOGRAPHY-MASS SPECTROMETRY ANALYSIS OF ESSENTIAL OIL, CYTOTOXIC EFFECT, AND ANTIMICROBIAL INVESTIGATION OF ROSMARINUS OFFICINALIS LEAVES. - Tawfeeq, Amani A; Mahdi, Monther F; Abaas, Ibrahim S; Alwan, Ali Hussein (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Rosmarinus officinalis L. is an aromatic perennial herb with fragrant evergreen needle-like leaves, and it is member species of Lamiaceae family raised from Mediterranean region. The aims of the study were isolation, quantification, and identification of rosmarinic acid of R. officinalis leaves and essential oil analysis using various chromatographic and spectroscopic methods, and also cytotoxic and antibacterial investigation against different species of bacteria. Methods: It was isolated by preparative HPLC and preparative TLC, and then it was determined by HPTLC. The identification and the structural elucidation of isolated rosmarinic acid were performed by H-nuclear magnetic resonance, electrospray ionization mass spectrometry (MS), infrared, and ultraviolet. Essential oil was analyzed by Gas Chromatography/Mass. Results: Results highlighted that rosmarinic acid content was 0.9% and the oil content was 1.8%, and R. officinalis chemotypes of Iraqi rosemary oil were camphor 23.04%, 1, 8-cineole 14.01%, and terpinen-4-ol 13.8%. The rosemary chemotype characterized as a high concentration of terpinen- 4-ol and good inhibition effect of rosemary methanolic extract against different species bacteria: Enterococcus faecalis, Staphylococcus saprophyticus, Acinetobacter baumannii, and Proteus mirabilis. Conclusions: The plant has a good content of rosemary phytochemicals and antibacterial effect, so the plantation of rosemary in Iraq has been successes. These isolated compounds are a suitable candidate for further clinical and pharmacological study.